Antioxidative Effects of Black Currant and Cornelian Cherry Juices in Different Tissues of an Experimental Model of Metabolic Syndrome in Rats - Marija Paunovic; Jelena Kotur-Stevuljevic; Aleksandra Arsic; Maja Milosevic; Vanja Todorovic; Azra Guzonjic; Vesna Vucic; Snjezana Petrovic (MDPI AG, 2023)
A Western-style diet, rich in fat and simple sugars, is the main risk factor for a significant number of chronic diseases and disorders, as well as for a progression of metabolic syndrome (MetS). One of the key mechanisms involved in MetS development is increased oxidative stress caused by the accumulation of body fat. Some dietary polyphenols have shown a protective role in preventing oxidative-stress-induced damage. We investigated the difference in the oxidative response of plasma, liver, and visceral adipose tissue in rats fed with a high-fat high-fructose (HFF) diet for ten weeks, and the effectiveness of polyphenol-rich juices (black currant (BC) and cornelian cherry (CC)) in HFF-diet-induced oxidative stress prevention. The most prominent impact of the HFF diet on redox parameters was recorded in the liver, whereas adipose tissue showed the most potent protection mechanisms against oxidative stress. Consumption of both juices decreased advanced oxidation protein product (AOPP) level in plasma, increased paraoxonase1 (PON1) activity in the liver, and significantly decreased total oxidative status (TOS) in adipose tissue. BC exerted stronger antioxidative potential than CC and decreased the superoxide anion radical (O2•−) level in the liver. It also reduced TOS, total antioxidative status (TAS), and malondialdehyde (MDA) concentration in adipose tissue. The multiple linear regression analysis has shown that the best predictors of MetS development, estimated through the increase in visceral adiposity, were superoxide dismutase (SOD), AOPP, TOS, and TAS. The consumption of polyphenol-rich juices may provide a convenient approach for the systemic reduction of oxidative stress parameters.